Mathematical Modelling and Optimization of Risk Analysis in Emergencies - A.M, Korneev; M.V, Salfetnikov (International Journal of Engineering and Technology, 2018)
In current work methods of intellectual support of acceptance of administrative decisions on risks of occurrence of extreme situations are considered. The relationship between human activity, the emergence emergencies and the state of the environment is systemic. An important role is given to the analysis of the causes of incidents and emergencies of technogenic nature. Emergencies refers to complex multi-level systems, so a systematic approach is needed to model them. When choosing models of complex systems, factors related to the natural properties of the constituent elements and subsystems, and the patterns of the functioning of the system as a whole are investigated. Various methods of mathematical modeling are used to determine the risks of emergencies. The problem of optimization of decision-making algorithms in the event of emergencies is solved.Â Â